Study of material recrystallized regions on deformation and cracking behaviours in cast steel brake discs. (October 2022) - Xie, Xiaodong; Li, Zhiqiang; Domblesky, Joseph P.; Yang, Zhiyong; Li, Weijing; Han, Jianmin
Graphical abstract: Highlights: Localized material recrystallized regions were characterized on serviced brake discs. In-situ tensile testing was conducted to analysis the material deformation and cracking behavior. The non-uniform distribution of grain boundary orientation lead to an "enhanced" strain localization. Abstract: Localized regions of recrystallized material have been observed on steel brake discs used in high-speed rail systems. Because the effects of recrystallized regions on steel brake disc cracking behaviour are not well known, further study is warranted. In the present study, the characteristics of localized regions of recrystallized material were characterized by transmission electron microscope, and the coupled effect of severe braking thermal cycles and frictional shear force was found to be the root cause of material recrystallization. In situ tensile testing was used to compare the deformation and cracking behaviours in samples taken from a in-service railway brake disc and a virgin brake disc. The results showed that the localized recrystallized material degrades the mechanical properties of the in-service brake disc due to strain localization. The localized recrystallization of the material also changed the sample fracture from a ductile mode in the virgin steel brake disc to a mixed mode. Electron back-scattered diffraction (EBSD) analysis showed that the nonuniform distribution of low angle grain boundaries (LAGBs) and high angle grain boundaries (HAGBs) in the localized recrystallized material reflected strain localization. HAGBs promoted local strengthening of the small-size grain region, resulting in grain-scale incompatibility deformation and enhanced strain localization. The difference in the degree of deformation between the large-size and small-size grain regions accordingly became irreconcilable, which led to stress concentrations and microcrack initiation. Based on these results, it was recommended that the microstructural condition of steel brake discs be monitored during maintenance inspections and that the sliding surfaces be turned to remove the recrystallized material if necessary.